Are some neutral liners more neutral than others? An ex vivo morphological analysis of acetabular liners classified as “neutral” - José Á Ochoa; Perttu S Neuvonen; Jari Hyttinen; Jari Viik; Antti P Eskelinen (Acta Orthopaedica, 2024)
Background and purpose: In contemporary total hip replacement (THR), dislocation is one of the most common complications. At our institution, the cause of an increase in the dislocation rate was recently reported to be reduced head coverage of a newly introduced neutral liner. We therefore aimed to ascertain whether differences exist in articulating head coverage between the various neutral liners used in contemporary THR. A secondary aim was to utilize coverage measurements to develop a new liner coverage classification. Methods: The articulating head coverage of 25 modular neutral polyethylene liners used in 6 uncemented cup designs from 4 major manufacturers was evaluated. The measurements were performed in a metrology laboratory and a mathematical model was developed to calculate coverage of the articulating surfaces. Further, 1 “elevated rim” liner and 1 “face changing liner” were included to develop a new liner coverage classification. Results: The articulating head coverage among the studied liners ranged from 167.7° to 194.8°, corresponding to a variation of 27.1°. The variations with different cup and head sizes within each design were smaller (from 1.0° to 5.6°) than those between different designs. Each of the liner designs offered distinct coverage, even though they were all classified as neutral. Based on measurements, a set of descriptive parameters to discriminate different liners in terms of coverage was created. Conclusion: We showed that all neutral liners are not equal – instead, they clearly varied in terms of their actual coverage design. We suggest our set of descriptive parameters called “hemispheric coverage index values” be used in discriminating the differences in liner coverage.